Better intestine health in fast‐growing bullfrogs (Lithobates catesbeianus) fed a soybean meal‐based diet than slow‐growing bullfrogs. (9th July 2022) - Tao, Bingyi; Wang, Zhe; Zhang, Chunxiao; Li, Xueshan; Lu, Kangle; Song, Kai; Wang, Ling; Rahimnejad, Samad
Abstract: This study examined the differences in intestinal health between fast‐ and slow‐growing bullfrogs ( Lithobates catesbeianus ) fed a soybean meal (SM)‐based diet. A total of 108 froglets (26.14 ± 0.21 g) were randomly distributed into three tanks at a density of 36 froglets per tank and fed a SM‐based diet for 8 weeks. At the end of the feeding period, four heaviest and four lightest bullfrogs from each tank were captured and considered as fast‐growing (FG) and slow‐growing (SG) groups. The FG group had significantly higher weight gain than the SG group ( p  < 0.05). A basic intestinal tissue structure integrity with higher values of jejunal diameter, villus numbers, villus thickness and muscular thickness was observed in the FG group compared with the SG group ( p  < 0.05). Moreover, lower activity of serum diamine oxidase was detected in FG group than the SG group, which indicated better gut barrier function of froglets in FG group ( p  < 0.05). However, no significant differences were found in the mRNA expression level of tight junction proteins including occludin and zo‐1 in the jejunum, and serum D‐lactate concentration between the two groups ( p  > 0.05). Significantly lower pH values in corpora ventriculi and ileum and higher jejunal protease and amylase activities were found in the FG group than SG group ( p  < 0.05). Relatively higher expression of anti‐inflammatory genes and lower expression of pro‐inflammatory genes were found in the FG group; however, the differences were not significant. The abundances of potential probiotics including Akkermansia, Lactobacillus and Prevotellaceae _ UCG _ 001 were higher in the intestinal microflora of FG group compared with the SG group. In conclusion, these findings suggested that higher growth of FG bullfrogs fed the SM‐based diet could be attributed to their better intestinal morphological structure and barrier function compared with the SG bullfrogs.